2023
DOI: 10.1111/twec.13399
|View full text |Cite
|
Sign up to set email alerts
|

Do deep regional trade agreements strengthen anti‐corruption? A social network analysis

Abstract: This paper adds to research on the international drivers of corruption and anti‐corruption by focusing on the influence of regional trade agreements (RTAs). Using cross‐national data and employing a social network analysis, we provide descriptions of the evolution of deep integration of RTAs' network in anti‐corruption and transparency with a comprehensive view in which we utilise the network's Closeness, Harmonic, Betweenness, Eigenvector, and PageRank centralities to demonstrate the positions of member count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…Research on enhancing the role of legal systems: X. Y. Zhang, R. K. Goel, J. M. Jiang and other scholars have proposed that causes related to anti-corruption or transparency within regional trade agreements could significantly impact the fight against public sector corruption in member countries [23]. L. R. Helfer and C. Rose suggested that a transnational asset recovery mechanism could enhance the rule of law system concerning international corruption [24].…”
Section: Literature Review 21 International Corruptionmentioning
confidence: 99%
“…Research on enhancing the role of legal systems: X. Y. Zhang, R. K. Goel, J. M. Jiang and other scholars have proposed that causes related to anti-corruption or transparency within regional trade agreements could significantly impact the fight against public sector corruption in member countries [23]. L. R. Helfer and C. Rose suggested that a transnational asset recovery mechanism could enhance the rule of law system concerning international corruption [24].…”
Section: Literature Review 21 International Corruptionmentioning
confidence: 99%